The Criminalization of Nitrous Oxide Abuse: A Comparative Study of Indonesian and Dutch Law - Kesya Nur Aulia Fernanda; Emmilia Rusdiana (ARBITER: Jurnal Ilmiah Magister Hukum, 2026)
The rising phenomenon of the misuse of nitrous oxide (N2O) as a recreational psychoactive substance has had an impact on public health and order. In contrast, Indonesia has yet to explicitly address its regulation in Law No.35 of 2009 concerning Narcotics. This study aims to examine the differences in regulations and the rationale for criminalizing N2O abuse as a legal reform in Indonesia, using a normative legal research method with statute, comparative, and conceptual approaches. This study found differences in the regulation of N2O abuse. The Netherlands has classified N2O as a category II controlled substance under the Dutch Opium Act (Opiumwet), which this study assesses as having considered the principles of ultimum remedium and proportionality. Meanwhile, Indonesia still lacks a comprehensive basis for criminalization. The relevance to legal reform in Indonesia lies in a phased approach. This study fills a gap in comparative research regarding the regulation of N2O abuse within legal systems in Indonesia and the Netherlands. These findings indicate the need for Indonesia to strengthen administrative regulations and oversight of the distribution and use of N2O. If non-penal instruments prove ineffective, criminalization may be considered selectively and in a manner that ensures proportionality.